Withdrawal and Discontinuation Phenomena Associated with Tranylcypromine: A Systematic Review - Gahr, M.; Schönfeldt-Lecuona, C.; Kölle, M. A.; Freudenmann, R. W. (Pharmacopsychiatry, 2013)
Tranylcypromine (TCP) is an effective antidepressant with a complex pharmacological profile and a relevant risk of abuse and dependence. Withdrawal phenomena (WP, in the case of TCP-abuse/dependence) or discontinuation phenomena (DP, in the case of absent TCP-abuse/dependence) subsequent to abrupt termination of TCP are a potentially severe clinical syndrome. We conducted a systematic review of all previously published WP/DP cases following abrupt termination of TCP in order to identify typical clinical presentations and risk factors of WP/DP and frequency of TCP abuse or dependence within these patients. By searching the Medline and Scopus databases we identified n=25 cases (cohort WP: n=18, cohort DP: n=7). Delirium was found in n=13 patients (cohort WP: 10/55.6%; cohort DP: 3/42.9%), n=6 demonstrated WP/DP without delirium (WP: 6/33.3%; DP: 0/0%) and n=5 rapid relapse in depression (WP: 1/5.6%; DP: 4/57.1%). Mean time until development of WP/DP was 1.9 (WP) and 2.2 (DP) days. Mean duration of WP/DP was 5.7 (WP) and 11.3 (DP) days. All patients of cohort WP were described to feature TCP-abuse/dependence. Patients with delirium were on average older (41.8 years vs. 37.8 years) and featured higher mean prescribed (71.0 mg vs. 38.3 mg) and actually taken daily TCP dosages (285.8 mg vs. 187.7 mg). In conclusion, even termination of lower daily dosages of TCP may result in delirium. Thrombocytopenia features diagnostic value in patients with deliria of unknown etiology. TCP should be administered with great care, especially in dependence-prone patients.·
Keywords: antidepressants; delirium; Jatrosom; Parnate; monoamine oxidase inhibitors; psychopharmacotherapy